Morphometric fruit traits of plants and morphometric traits of birds on Kilimanjaro - Maximilian Vollstaedt; Stefan W Ferger; Andreas Hemp; Kim M Howell; T Töpfer; Katrin Böhning-Gaese; Matthias Schleuning (PANGAEA, 2018)
Climate change and an increase in human disturbance are major drivers of global biodiversity loss. Yet it is not clear to what extent their effects on animal communities are direct or indirectly mediated by changes in biotic factors, such as plant diversity. Here, we disentangle the direct and indirect effects of climate, human disturbance, vegetation structure and plant functional traits on the functional diversity of avian frugivore communities across a large environmental gradient.We sampled plant and bird communities along an elevational and a human disturbance gradient and measured corresponding morphological traits of plants and birds to calculate indices of functional identity and functional diversity of plant and bird communities. We used structural equation models to disentangle direct and indirect effects of all variables on functional identity and diversity of frugivorous bird communities. Both functional identity and diversity of frugivorous bird communities were consistently related to the functional identity and diversity of plant communities. Climate had almost exclusively indirect effects on functional identity and diversity of bird communities mediated through effects on plant functional identity and diversity. In contrast, human disturbance also had direct negative effects on bird diversity.We show that plant functional identity and diversity are the most important drivers of functional identity and diversity of frugivorous birds. Although effects of climate on bird communities are almost exclusively mediated indirectly through plant communities, human disturbance resulted in a direct reduction of bird diversity. The high degree of trait matching between interdependent trophic levels over a large environmental gradient demonstrates the importance of biotic drivers for animal communities and shows that biodiversity models need to consider such bottom-up effects in future conditions.
Supplement to: Vollstaedt, M et al. (2017): Direct and indirect effects of climate, human disturbance and plant traits on avian functional diversity. Global Ecology and Biogeography, 26(8), 963-972, https://doi.org/10.1111/geb.12606